Eating disorders: When social rank perceptions are shaped by early shame experiences - Matos, Marcela (2015)
Recent research has shown that early adverse experiences can be an important risk factor for eating disorders. However, the role of early shame memories and how they are structured as traumatic and central memories to self-identity in eating disorders has never been investigated. This study explores the phenomenology of shame memories involving attachment figures and other agents from the wider social domain in patients with eating disorders, and examines the relationship between their traumatic and centrality features, social comparison based on physical appearance, and the severity of eating psychopathology.